Cell surface transport, oligomerization, and endocytosis of chimeric type II glycoproteins: role of cytoplasmic and anchor domains. - Kundu, A (1991)
We investigated the role of cytoplasmic and anchor domains of type II glycoproteins in intracellular transport, oligomerization, and endocytosis by expressing the wild-type and chimeric genes in mammalian cells. Chimeric genes were constructed by exchanging the DNA segments that encode the cytoplasmic and anchor domains between the human influenza virus (A/WSN/33) neuraminidase (NA) and transferrin receptor (TR). The chimeric proteins in which domains were exchanged precisely were productively targeted to the cell surface. However, the proteins appeared to assemble differently in the intracellular compartment. For example, while TR existed predominantly as a dimer, NATR delta 90, containing the cytoplasmic and signal-anchor domains of NA and the ectodomain of TR, was present as a tetramer, a dimer, and a monomer. Similarly, the influenza virus NA existed predominantly as a tetramer but TRNA delta 35, in which the cytoplasmic and signal-anchor domains of TR were joined to the ectodomain of NA, existed predominantly as a dimer, suggesting that the cytoplasmic and anchor domains of type II glycoproteins affect the subunit assembly of heterologous ectodomains. In addition, we analyzed the role of the cytoplasmic domain in endocytosis. NA and NATR delta 90 did not undergo endocytosis, whereas both TR and TRNA delta 35 were internalized efficiently, demonstrating that the NH2 cytoplasmic domain of TR was capable of internalizing a heterologous ectodomain (NA) from the cell surface.